2013
DOI: 10.4236/jbbs.2013.37053
|View full text |Cite
|
Sign up to set email alerts
|

Human-Related Emotional Stimuli Can Cause a Hippocampal and Thalamic Over-Response in People with Unstable Personalities

Abstract: Hippocampus is crucial for the formation of emotional memory. We found the relationship between hippocampal responses to emotional stimuli and the mental stabilities of people in our preliminary study. In this study, we have also evaluated how the emotional stimuli would affect amygdala and thalamus in the brain, and how the personality stabilities could relate to the responses in the brain using functional magnetic resonance imaging (fMRI). We evaluated the subjects' personality features with the Yatabe-Guilf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…It is worth mentioning that another explanation for these changes in FC might involve the thalamus directly. Studies have shown that hyperactivation of the thalamus might be associated with an increase in emotional distress and dysregulation (Geng et al, 2018;Mizuno-Matsumoto et al, 2013). Our results suggest that thalamus is recruiting dlPFC and vmPFC for regulation, as it is known to happen in other studies (Hutcherson et al, 2012).…”
Section: Discussionsupporting
confidence: 57%
“…It is worth mentioning that another explanation for these changes in FC might involve the thalamus directly. Studies have shown that hyperactivation of the thalamus might be associated with an increase in emotional distress and dysregulation (Geng et al, 2018;Mizuno-Matsumoto et al, 2013). Our results suggest that thalamus is recruiting dlPFC and vmPFC for regulation, as it is known to happen in other studies (Hutcherson et al, 2012).…”
Section: Discussionsupporting
confidence: 57%
“…Second, high anxious individuals showed stronger thalamus activation in the uncertain threat condition. Given the aforementioned role of the thalamus in rapid emotional processing, this finding suggests that when facing uncertain threat situations, high anxious individuals engage stronger and more rapid anticipatory emotional reaction (Mizuno‐Matsumoto et al, ). This statement is supported by previous behavioral studies which found that anxious individuals showed intense emotional reactions (i.e., startle) during the anticipation of uncertain threat than the certain condition (Grillon et al, ; Shankman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that high anxious individuals showed stronger activations in the thalamus, PHA, dlPFC, and IPS, which are important for both emotional processing and cognitive control. The thalamus is a core hub in the ‘low road’ emotional path, which is critical for automatic processing of emotional stimulus (Mizuno‐Matsumoto et al, ; Pessoa & Adolphs, ). Increased activation of the thalamus in this study may indicate rapid “high‐way” emotional reaction during the anticipation of the future.…”
Section: Discussionmentioning
confidence: 99%
“…When the emotional stimuli are treated in the brain, the pleasant and unpleasant emotional information could be processed in different ways . First, all kinds of emotional stimuli could be assessed to see whether the stimuli are pleasant or unpleasant in the amygdala.…”
Section: Discussionmentioning
confidence: 99%